BOPO, NPF, INFLASI, SUKU BUNGA ACUAN BANK INDONESIA, DAN PROFITABILITAS BANK SYARIAH DI INDONESIA - Lina Marlina; Wulandari Wahyu Hidayat; Biki Zulfikri Rahmat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
A Sharia Financial Institution (LKS) is a financial institution whose operational principles are based on sharia principles which must avoid elements of usury, gharar, maisir and false contracts. The purpose of this study was to determine the effect of BOPO, NPF, Inflation and Bank Indonesia's Reference Interest Rate on the profitability of Islamic Commercial Banks in Indonesia (Period 2014 2018) partially and simultaneously. This study uses a quantitative approach. The data collection technique in this study was carried out using the documentation method, namely by collecting, recording and reviewing secondary data in the form of quarterly financial reports for Islamic Commercial Banks from 2014-2018. Variable Cost of Operational Income (BOPO) has a significant negative effect on the Profitability of Islamic Commercial Banks in Indonesia (2014-2018), Non Performing Financing has a significant negative effect on Profitability and Bank Indonesia's Reference Interest Rate has a significant negative effect on Profitability of Islamic Commercial Banks, This means that an increase in the BOPO, NPF and Bank Indonesia Reference Interest Rate can reduce the Profitability of Islamic Commercial Banks in Indonesia. Meanwhile, inflation did not have a significant effect.